PCP‐B class pollen coat proteins are key regulators of the hydration checkpoint in Arabidopsis thaliana pollen–stigma interactions - Wang, Ludi (New Phytol, 2016)
The establishment of pollen–pistil compatibility is strictly regulated by factors derived from both male and female reproductive structures. Highly diverse small cysteine‐rich proteins (CRPs) have been found to play multiple roles in plant reproduction, including the earliest stages of the pollen–stigma interaction. Secreted CRPs found in the pollen coat of members of the Brassicaceae, the pollen coat proteins (PCPs), are emerging as important signalling molecules that regulate the pollen–stigma interaction. Using a combination of protein characterization, expression and phylogenetic analyses we identified a novel class of Arabidopsis thaliana pollen‐borne CRPs, the PCP‐Bs (for pollen coat protein B‐class) that are related to embryo surrounding factor (ESF1) developmental regulators. Single and multiple PCP‐B mutant lines were utilized in bioassays to assess effects on pollen hydration, adhesion and pollen tube growth. Our results revealed that pollen hydration is severely impaired when multiple PCP‐Bs are lost from the pollen coat. The hydration defect also resulted in reduced pollen adhesion and delayed pollen tube growth in all mutants studied. These results demonstrate that At PCP‐Bs are key regulators of the hydration ‘checkpoint’ in establishment of pollen–stigma compatibility. In addition, we propose that interspecies diversity of PCP‐Bs may contribute to reproductive barriers in the Brassicaceae.